Evaluation of Analgesic Effects of Different Doses of Vitamin D3 in Two Animal Models of Pain in Swiss Albino Mice - Shakeeb Siraj Dhorajiwala; Rajan P. Nerurkar; Kanchan R. Singh (Indian Journal of Pain)
Background and Objective: Pain is the most common symptom compelling an individual to seek medical attention. The use of Vitamin D3 for nociceptive and inflammatory pain is highly debated. Therefore, this study was undertaken to compare three daily doses (15/30/60 μg/kg) and a single high dose of Vitamin D3 (260 μg/kg) to standard drugs, namely tramadol and diclofenac in two most resorted pain-models in mice. Materials and Methods: Thirty-six Swiss-albino mice were divided into six groups of six mice each. The experiment was conducted using hot plate and writhing test. Same groups of mice were reused after suitable wash-out period. Groups were dosed with 0.25% carboxymethyl-cellulose (negative-control), a positive-control (tramadol for hot-plate and diclofenac for writhing-test). Injection Vitamin D3 was given in three daily doses of 15/30/60 μg/kg. Single dose of 260 μg/kg of Vitamin D3 was also tested. Latency period (LP), percent of maximal-possible-antinociceptive-effect (%MPE), mean number and percentage inhibition of writhes were the parameters evaluated to compare analgesic effect. Data were analyzed using paired t-test, analysis of variance (ANOVA)/Kruskal–Wallis/Friedman’s-ANOVA, and repeated-measures ANOVA with post hoc Dunnett’s tests. Results: In hot-plate method, 60 and 260 μg/kg of Vitamin D3 raised mean LP when compared to baseline and negative control and all groups recorded higher percentage MPE values when compared to negative control. In writhing test, 15-, 30-, and 60 μg/kg/day showed analgesic effect in comparison to negative control. However, 15 and 30 μ/kg/day of Vitamin D3 contradicted its responses when assessed through different parameter. Interpretation and Conclusion: In hot-plate test, 60 and 260 μg/kg of Vitamin D3 showed significant analgesic effect; however, effects were not superior to tramadol. In writhing test, 15-, 30-, and 60 μg/kg/day showed significant analgesic effect which were not superior to diclofenac. Surprisingly, 15 and 30 μ/kg, on instances exhibited irritant effects.